Long‐Stay Nursing Facility Resident Transfers: Who Gets Admitted to the Hospital?. Issue 9 (6th July 2020) - Unroe, Kathleen T.; Caterino, Jeffrey M.; Stump, Timothy E.; Tu, Wanzhu; Carnahan, Jennifer L.; Vest, Joshua R.; Sachs, Greg A.; Hickman, Susan E.
Abstract : BACKGROUND/OBJECTIVES: The Optimizing Patient Transfers, Impacting Medical Quality, and Improving Symptoms: Transforming Institutional Care (OPTIMISTIC) project is a successful, multicomponent demonstration project to reduce potentially avoidable hospitalizations of long‐stay nursing facility residents. To continue to reduce hospital transfers, a more detailed understanding of these transfer events is needed. The purpose of this study was to describe differences in transfer events that result in treatment in the hospital versus emergency department (ED) only. DESIGN: OPTIMISTIC project nurses collected data on residents who transferred. Transfer events that resulted in treatment in ED versus hospitalization were compared using t ‐tests and chi‐square tests. A generalized estimating equations regression model was used to assess the associations between hospital admission and transfer characteristics. PARTICIPANTS: A total of 867 long‐stay nursing facility residents enrolled in OPTIMISTIC, January 2015 to June 2016. MEASUREMENTS: Resident and transfer characteristics from Minimum Data Set and project REDCap (Research Electronic Data Capture) database, including demographics, cognitive status, comorbidities, symptoms at time of transfer, and diagnoses. RESULTS: The most common symptoms associated with treatment in the ED only were falls, trauma, or fracture (38% vs 10% admitted). Residents with cognitive impairment were more likely to be admitted to the hospital (odds ratio (OR) = 1.47; 95% confidence interval (CI) = 1.09–1.98; P  = .011). Residents with respiratory complaints were more likely to be admitted (OR = 2.098; 95% CI = 1.198–3.675; P  = .009); residents with hematological/bleeding (nongastrointestinal) (OR = 0.23; 95% CI = 0.107–0.494; P = .0002), pain (OR = 0.421; 95% CI = 0.254–0.698; P  = .0008), or fall/trauma/fracture (OR = 0.181; 95% CI = 0.12–0.272; P < .001) were less likely to be admitted to the hospital. CONCLUSION: Some presenting symptoms and other characteristics are more associated with ED only treatment versus hospitalization. A knowledge of who is likely to receive ED only care could prompt adoption of targeted resources and protocols to further reduce these types of transfer events. Opportunity may exist in the ED as well to reduce hospitalizations and increase discharges back to the facility.